2011
DOI: 10.1111/j.1095-8312.2010.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Modularity in attachment organs of African Cichlidogyrus (Platyhelminthes: Monogenea: Ancyrocephalidae) reflects phylogeny rather than host specificity or geographic distribution

Abstract: Cichlidogyrus spp. (Monogenea, Ancyrocephalidae) are common parasites of cichlid fishes from Africa and the Levant. They display important morphological variation in their attachment apparatus and infect a broad host spectrum throughout a wide geographic range. Thus, they offer an interesting model to investigate to what extent the phenotypic variability of the attachment organ among congeners is related to host specificity, geographic/ environmental components, or phylogeny. A geometric morphometric approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(152 citation statements)
references
References 69 publications
7
143
1
1
Order By: Relevance
“…3). The 71 species of Cichlidogyrus presently described from Africa and the Levant can be clustered in four morphological groups, according to the length of their uncinuli (POUYAUD et al 2006, PARISELLE & EUZET 2009, VIGNON et al 2011. Cichlidogyrus vandekerkhovei sp.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The 71 species of Cichlidogyrus presently described from Africa and the Levant can be clustered in four morphological groups, according to the length of their uncinuli (POUYAUD et al 2006, PARISELLE & EUZET 2009, VIGNON et al 2011. Cichlidogyrus vandekerkhovei sp.…”
Section: Figmentioning
confidence: 99%
“…However, despite the great number of studies on Cichlidae of Lake Tanganyika, studies on their parasite fauna, especially on their monogenean flatworms, are practically inexistent as in many tropical biomes throughout the world (WHITTINGTON 1998, BAKKE et al 2002, HUYSE et al 2006, VANHOVE et al 2011). However, monogeneans are known to depict a considerable biological diversity -the average number of species per host is more than six in West Africa (PARISELLE et al 2003b) -and they usually depict high host specificity, parasitizing a single or few closely related host species.…”
mentioning
confidence: 99%
“…The shape changes modelled onto a TPS can be separated into two parts, the uniform and non-uniform components (Rohlf and Slice, 1990). The former (U1 and U2) express global variations in shape, whereas the latter describe local shape changes at different geometric scales (Vignon et al, 2011). To visualize localized anchor shape differences, TPS deformation grids and grey-scaled coded Jacobian expansion factors, which measure the degree of local expansion or contraction of the grid (black for factors >1, indicating expansion; grey for factors between 0 and 1, indicating contraction) were used (Bookstein, 1993;Viscosi and Cardini, 2011).…”
Section: Geometric Morphometricsmentioning
confidence: 99%
“…This coordination among parts of the haptor could be due to host specificity and the attachment mechanism (Vignon et al, 2011). Klingenberg (2008) suggested that this kind of morphological covariationcan be a substantial player determining the evolutionary potential of traits within populations.…”
Section: Ligophorus Llewellynimentioning
confidence: 99%
See 1 more Smart Citation